Multifactorial assessment and targeted intervention in nutritional status among the older adults: a randomized controlled trial: the Octabaix study - Badia, Teresa (BMC Geriatr, 2015)
BACKGROUND: Malnutrition is frequent among older people and is associated with morbi-mortality. The aim of the study is to assess the effectiveness of a multifactorial and multidisciplinary intervention in the nutritional status among the elderly. METHODS: Randomized, single-blind, parallel-group, clinical trial conducted from January 2009 to December 2010 in seven primary health care centers in Baix Llobregat (Barcelona). Of 696 referred people, born in 1924, 328 subjects were randomized to an intervention group or a control group. The intervention model used an algorithm and was multifaceted for both the patients and their primary care providers. The main outcome was improvement in nutritional status assessed by Mini Nutritional Assessment (MNA). Data analyses were done by intention-to-treat. RESULTS: Two-year assessment was completed for 127 patients (77.4%) in the intervention group and 98 patients (59.7%) in the control group. In the adjusted linear mixed models for MNA, intervention showed no significant effect during all follow-up period with −0.21 (CI: − 0.96; 0.26). In subjects with nutritional risk (MNA ≤ 23.5 / 30) existed a tendency towards improvement in MNA score 1.13 (95% CI −0.48; 2.74) after 2 years. CONCLUSION: A universal multifactorial assessment and target intervention over a two year period in subjects at nutritional risk showed a tendency to improve nutrition but not in the rest of community-dwelling studied subjects. Cognitive impairment was an independent factor strongly associated with a decline in nutritional status. TRIAL REGISTRATION: The clinical trial is registered as part of a US National Institutes of Health Clinical Trial: NCT01141166. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12877-015-0033-0) contains supplementary material, which is available to authorized users.